Faktor Risiko Tuberkulosis Paru Anak di RSUD DR. LA Palaloi Maros Periode 2019 - 2023 - Salsabila, Oryza Camilia; Madjid, Djauhariah; Gani, Sri Wahyuni Saraswati; Darma, Sidrah; Jafar, Muh. Alfian (Innovative: Journal Of Social Science Research, 2024)
Tuberculosis (TB) is a contagious disease that remains one of the leading causes of death worldwide and can affect children. Over time, significant changes have occurred in TB control efforts, necessitating a re-evaluation of the risk factors for tuberculosis in children. This study aims to identify the risk factors for pediatric pulmonary tuberculosis at RSUD dr. La Palaloi Maros from 2019 to 2023. This study used an observational analytic design with a cross-sectional method, utilizing secondary data from medical records of pediatric pulmonary TB patients at RSUD dr. La Palaloi Maros from 2019 to 2023. The sampling technique employed was purposive sampling. Of the 89 cases of pediatric pulmonary TB, based on age, the majority (53.9%) were 5-11 years old. Based on gender, most were male (55.1%). Regarding BCG immunization history, 57.3% had been immunized. In terms of nutritional status, 39.3% were found to have good nutritional status. Additionally, 79.8% of the samples had a history of contact with TB patients. The majority of parents were from low-income occupational groups (36.0%). Among these risk factors, a bivariate Chi-square analysis was conducted, yielding a significant p-value (<0.05) for nutritional status. In multivariate analysis, nutritional status was also found to be the most influential factor in pediatric pulmonary TB, increasing the risk by 0.096 times (CI: 0.037-0.252). In this study, the most significant risk factor was nutritional status.